Total synthesis of (−)-epimyrtine by a gold-catalyzed hydroamination approach - Trinh, Thi Thanh Huyen; Nguyen, Khanh Hung; de Aguiar Amaral, Patricia; Gouault, Nicolas (Beilstein Journal of Organic Chemistry, 2013)
A new approach to the total synthesis of (−)-epimyrtine has been developed from D-alanine. The key step to access the enantiopure pyridone intermediate was achieved by a gold-mediated cyclization. Finally, various transformations afforded the natural product in a few steps and good overall yield.
Keywords: epimyrtine; gold; gold catalysis; heterocycles; hydroamination; quinolizidine alkaloid; total synthesis